Advantages of Using Innovative Technologies in Teaching the Laws of Dynamics in Physics Lessons - Abdunabiyeva Maftunakhan Solijon kizi (International Journal on Integrated Education, 2022)
This article describes ways and problems of improving the educational process, modeling physics lessons, and the main features of computer-based teaching technology. In addition, the advantages of using virtual laboratories and the modeling of physical phenomena in the Visual Basic program are analyzed.